Editorial Vol. 10, No. 2, December 2022 - Fentiny Nugroho, Ph.D (Indonesian Social Work Consortium (ISWC), 2022)
Welcome to Open Journal System of ASEAN Social Work Journal Vol. 10, No. 2, December 2022. It is a double-blind peer-reviewed, open-access journal. Previously, the journal Volume one to nine were published in two versions: printed and online versions uploaded to the website of ASEAN Social Work Consortium (ASWC). Starting from Vol. 10, No. 1, June 2022 we also applied an Open Journal System (OJS), in the hope that readers and the spread of authors’ research would be much broader. The birth of this journal is a significant part of the dynamic movement among ASEAN country members. This publication is an implementation of the workplan formulated at the first meeting of ASEAN Social Work Consortium (ASWC) in Manila in the year of 2011. Social work around the world, especially in ASEAN countries, is facing new challenges and roles as the impact of covid-19 pandemic. The loss of the parets’role because they die due to covid-19, digitalization in all aspects of life, both business and social life because during the pandemic people have to do activities from home, so digitalization has become a new habit; people are also increasingly individualized because during the covid-19 pandemic they have to keep distance, even though the ASEAN communities generally have strong ties. Although at present the pandemic is becoming better, however, it has already caused major changes in people's lives. Social workers as agents of change are needed to support communities to learn and practice new norms and life skills as a result of the covid-19 pandemic. Only if people can adapt to new ways of life, then people can survive and be socially functioning On behalf of the Indonesian Social Work Consortium (ISWC), we are thanking all of you for your support and contribution as the Editors/Reviewers and Authors. We would also like to express our gratitude for the great support of the ASEAN Secretariat, Project Management Unit/Indonesian Independent Social Worker, UNICEF and the Ministry of Social Affairs. Editor-in-Chief, Fentiny Nugroho